2009
DOI: 10.1080/00221686.2009.9522006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigations of dike-break induced flows

Abstract: Experimental model data are compared with numerical computations of dike-break induced flows, focusing on the final steady state. An idealized scale model was designed reproducing the specific boundary conditions of dike breaks. Discharges, water level, and depth profiles of horizontal velocities were recorded and validated by numerical modeling. The latter was performed by two different models solving the two-dimensional depth-averaged shallow water equations, namely a total variation diminishing Runge-Kutta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
1
33
0
5
Order By: Relevance
“…Fe et al 17) indicated that the conventional, water depth-based formula fails to handle subcritical flows with re-circulation zones, which on the other hand are reasonably well simulated using the hydraulic radius-based counterpart. The corrected Manning's formulae proposed in Dewals et al 18) and Roger et al 19) are essentially same with that of Brufau and Garcia-Navarro 16) . As indicated in the literatures, the choice of the friction slopes is significant for open channel flows.…”
Section: Introductionsupporting
confidence: 65%
“…Fe et al 17) indicated that the conventional, water depth-based formula fails to handle subcritical flows with re-circulation zones, which on the other hand are reasonably well simulated using the hydraulic radius-based counterpart. The corrected Manning's formulae proposed in Dewals et al 18) and Roger et al 19) are essentially same with that of Brufau and Garcia-Navarro 16) . As indicated in the literatures, the choice of the friction slopes is significant for open channel flows.…”
Section: Introductionsupporting
confidence: 65%
“…On the one hand, our original iterative approach has been used so far in a number of flow studies involving wetting and drying of cells [6,17,18]. On the other hand, it may also apply for suspended load modelling accounting for a variation range of the concentration bounded by zero and a saturation concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Entièrement développé au sein de l'unité de recherches du HACH à l'Université de Liège, il a été validé et exploité sur la modélisation de plus de 1000 km de rivière en Belgique. WOLF2D résout les équa-tions en eaux peu profondes par un schéma volumes finis [17][18][19][20][21]. La combinaison du modèle bidimensionnel avec une topographie LIDAR à une résolution de 2 mètres en fait un outil idéal pour modéliser des crues dans les environnements urbains.…”
Section: Iv3 Modélisation Hydrodynamique De La Crueunclassified